Nanoaptasensor development based on gold nanotriangles for the detection of aflatoxin B1 by LSPR - Veliz Portal, Lorena (2020)
Aflatoxin B1 (AFB1) is one of the most frequent mycotoxins produced by certain species of the fungi Aspergillus, which affects a wide variety of agricultural products such as kiwicha. AFB1 is known to be nephrotoxic, hepatotoxic and carcinogenic, and has led to strict regulation throughout the world and the need to have new rapid, simple and selective methods to detect the mycotoxin. The nanoaptasensors based on gold nanotriangles (AuNTs) emerge as a simple and effective alternative to traditional detection systems. On the one hand, aptamers make the system stable and very selective due to its high affinity, but at a low cost. On the other hand, the exceptional optical properties of gold nanoparticles allow the implementation of the sensor in a simple analytical technique such as UV-Vis-NIR spectroscopy. This development is possible due to the localized surface plasmon resonance (LSPR), which allows monitoring the interaction between the aptamer and the toxin and correlating the spectral changes with the mycotoxin content. The sensitivity of the nanosensors was evaluated in different solvents and buffers within the 0-780 ppbs AFB1 range. Best results were obtained using PBS buffer with MgCl2 pH 7.5 (R2 = 0.98101). Furthermore, the spectral analysis by the partial least squares regression (PLS) method it was possible to achieve a detection limit of 22 ppbs. Finally, the developed nanoaptasensors have shown good responses even in the presence of a complex matrix such as kiwicha.